PEGASO: An ultra light long duration stratospheric payload for polar regions flights - Iarocci, A.; Benedetti, P.; Caprara, F.; Cardillo, A.; Di Felice, F.; Di Stefano, G.; Drakøy, P.; Ibba, R.; Mari, M.; Masi, S.; Musso, I.; Palangio, P.; et al. (Advances in Space Research, 2006)
Stratospheric balloons are powerful and affordable tools for a wide spectrum of scientific investigations that are carried out at the stratosphere level. They are less expensive compared to satellite projects and have the capability to lift payloads from a few kilograms to a couple of tons or more, well above the troposphere, for more than a month. Another interesting feature of these balloons, which is not viable in satellites, is the short turnaround time, which enables frequent flights. We introduce the PEGASO (Polar Explorer for Geomagnetism And other Scientific Observations) project, a stratospheric payload designed and developed by the INGV (Istituto Nazionale di Geofisica e Vulcanologia), Rome and La Sapienza University, Rome. The project was sponsored by the PNRA (Progetto Nazionale di Ricerche in Antartide), Italy (Peterzen et al., 2003). This light payload (10 kg) was used by the Italian Space Agency (ASI) and Andoya Rocket Range (ARR) for five different scientific missions. PEGASO carries a 3-component flux-gate magnetometer, uses a solar cell array as the power source and has a GPS location system. The bi-directional telemetry system for data transfer and the remote control system were IRIDIUM based INGV, PNRA, ASI, ARR, CNR, La Sapienza, In press 1.10. TTC - Telerilevamento JCR Journal open